2012
DOI: 10.1088/0957-0233/23/10/105501
|View full text |Cite
|
Sign up to set email alerts
|

Basics of broadband impedance spectroscopy measurements using periodic excitations

Abstract: Measuring the impedance frequency response of systems by means of frequency sweep electrical impedance spectroscopy (EIS) takes time. An alternative based on broadband signals enables the user to acquire simultaneous impedance response data collection. This is directly reflected in a short measuring time compared to the frequency sweep approach. As a result of this increase in the measuring speed, the accuracy of the impedance spectrum is compromised. The aim of this paper is to study how the choice of the bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 64 publications
0
79
0
Order By: Relevance
“…A logarithmic analysis carried out between 0.01 and 10 Hz with five frequencies needs 276 s to be completed, this includes the calculation time [75]. Sanchez et al [76] stated that real time processing, accuracy and the ability of data retrieval and throughput of a BIS system were the most important features to be applied in health monitoring systems, and Sanchez et al [77] introduced a local polynomial based method for impedance-frequency-response estimation.…”
Section: Fundamentals Of Bioimpedance Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…A logarithmic analysis carried out between 0.01 and 10 Hz with five frequencies needs 276 s to be completed, this includes the calculation time [75]. Sanchez et al [76] stated that real time processing, accuracy and the ability of data retrieval and throughput of a BIS system were the most important features to be applied in health monitoring systems, and Sanchez et al [77] introduced a local polynomial based method for impedance-frequency-response estimation.…”
Section: Fundamentals Of Bioimpedance Measurement Techniquesmentioning
confidence: 99%
“…Sanchez et al [76] stated that real time processing, accuracy and the ability of data retrieval and throughput of a BIS system were the most important features to be applied in health monitoring systems, and Sanchez et al [77] introduced a local polynomial based method for impedance-frequency-response estimation. Comparison studies between four different multi-sine periodic broadband excitations broadband for EIS measurements in term of accuracy and speed in frequency and time domain concluded that multi-sine and discrete interval binary sequences (DIBS) enhance SNRZ and have better accuracy than chirp and maximum length binary sequences (MLBS) [75]. …”
Section: Fundamentals Of Bioimpedance Measurement Techniquesmentioning
confidence: 99%
“…But, the increase in measurement speed can cause the loss of the accuracy [12]. In next section, a study of signal's parameters and the effect of their variation on the excitation are expounded.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The CF [10] is expressed in (3), wherein T denotes the observation time of the voltage or current signal, s(t) and a divisor in this equation represents the RMS value of the signal:…”
Section: B Signal-to-noise Ratio and Crest Factormentioning
confidence: 99%
“…Optimization of multisine with 11 components i = [1,2,3,4,5,6,7,8,9,10,11] gives CF = 1.372 at optimal phases In the case where all the initial phases are zero, the CF increases to 2.39 (only 3.42 % higher in comparison with optimal phases).…”
Section: ) Examplementioning
confidence: 99%